HIV Infection Itself May Not Be Associated With Subclinical Coronary Artery Disease Among African Americans Without Cardiovascular Symptoms. Issue 3 (24th March 2016) - Lai, Hong; Moore, Richard; Celentano, David D.; Gerstenblith, Gary; Treisman, Glenn; Keruly, Jeanne C.; Kickler, Thomas; Li, Ji; Chen, Shaoguang; Lai, Shenghan; Fishman, Elliot K.
Abstract : Background: The key objectives of this study were to examine whether HIV infection itself is associated with subclinical coronary atherosclerosis and the potential contributions of cocaine use and antiretroviral therapies (ARTs) to subclinical coronary artery disease (CAD) in HIV‐infected persons. Methods and Results: Between June 2004 and February 2015, 1429 African American (AA) adults with/without HIV infection in Baltimore, Maryland, were enrolled in an observational study of the effects of HIV infection, exposure to ART, and cocaine use on subclinical CAD. The prevalence of subclinical coronary atherosclerosis was 30.0% in HIV‐uninfected and 33.7% in HIV‐infected ( P =0.17). Stratified analyses revealed that compared to HIV‐uninfected, HIV‐infected ART naïve were at significantly lower risk for subclinical coronary atherosclerosis, whereas HIV‐infected long‐term ART users (≥36 months) were at significantly higher risk. Thus, an overall nonsignificant association between subclinical coronary atherosclerosis and HIV was found. Furthermore, compared to those who were ART naïve, long‐term ART users (≥36 months) were at significantly higher risk for subclinical coronary atherosclerosis in chronic cocaine users, but not in those who never used cocaine. Cocaine use was independently associated with subclinical coronary atherosclerosis. Conclusions: Overall, HIV infection, per se, was not associated with subclinical coronary atherosclerosis in this population. Cocaine use was prevalent in both HIV‐infected and ‐uninfected individuals and itself was associated with subclinical disease. In addition, cocaine significantly elevated the risk for ART‐associated subclinical coronary atherosclerosis. Treating cocaine addiction must be a high priority for managing HIV disease and preventing HIV/ART‐associated subclinical and clinical CAD in individuals with HIV infection.